2018
DOI: 10.1055/s-0038-1625958
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes Following Low-Profile Mesh Plate Osteosynthesis of Patella Fractures

Abstract: Treatment of patella fractures is fraught with complications and historically poor functional outcomes. A fixation method that allows for early mobilization and decreases symptomatic hardware rates will improve knee range of motion, postoperative functional status, and reoperation rates. The purpose of this study was to evaluate the functional outcomes after locked plate osteosynthesis of patella fractures at a Level 1 trauma center. A retrospective case series was conducted of patients who underwent open redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 25 publications
0
23
0
7
Order By: Relevance
“…Tension band wiring has been widely used in the treatment of patella fractures, however, it is associated with poor functional outcome and surgical complications, including a high rate of implant removal (3)(4)(5). Recently, a number of studies demonstrated that low-profile plating could fix patella fractures rigorously and improve postoperative knee function, particularly in comminuted patella fracture patterns (6)(7)(8). It also should be noted that plates may be bulky and irritate soft tissues, thus increasing the risk of wound healing problems.…”
Section: Introductionmentioning
confidence: 99%
“…Tension band wiring has been widely used in the treatment of patella fractures, however, it is associated with poor functional outcome and surgical complications, including a high rate of implant removal (3)(4)(5). Recently, a number of studies demonstrated that low-profile plating could fix patella fractures rigorously and improve postoperative knee function, particularly in comminuted patella fracture patterns (6)(7)(8). It also should be noted that plates may be bulky and irritate soft tissues, thus increasing the risk of wound healing problems.…”
Section: Introductionmentioning
confidence: 99%
“…The complication rate of other studies on anterior locking plate fixation of the patella ranges from 0% to19% 26 , 27 , 28 , 29 , 34 , 35 , 36 . Apart from the leading complication of infections (27%), there was also a loss of reduction with avulsion of the inferior pole (36%).…”
Section: Discussionmentioning
confidence: 93%
“…Die Komplikationsrate anderer Untersuchungen zur winkelstabilen Plattenosteosynthese der Patella liegt bei 0 – 19% 26 , 27 , 28 , 29 , 34 , 35 , 36 . Dabei finden sich neben Infektionen (27% der Komplikationen) als führende Komplikation ein Repositionsverlust mit Ausriss eines distalen Polfragmentes (36%).…”
Section: Diskussionunclassified
“…[3] Osteoporotic bone, comminuted fractures, and inferior pole fractures, as demonstrated in our case series, are scenarios where plates can function as an adjunct to more common fixation methods. [7–13]…”
Section: Discussionmentioning
confidence: 99%